Determination of Mandibular Condylar Uptake in Asymptomatic Populatio - Fatima, Raana; Hussain, Fida; Dar, Zaigham Salim; Nouman, Muhammad Inamullah; Sharoon, Rebecca; Raza, Mehdi (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine mandibular condylar uptake values in normal population through quantitative analysis employing Tc-99m MDP SPECT/CT.Study Design:  Cross-sectional study.Place and Duration of study: Nuclear Medical Centre, Armed Forces Institute of Pathology, Rawalpindi, Pakistan, from Jul 22 to Jul 23.Methodology: A total of 129 individuals, both genders aged 10 to 40 years, with no known skull pathology, were included in the study. Quantitative analysis of Tc-99m MDP SPECT/CT bone scan of asymptomatic population was used to calculate mandibular condyle to clivus ratio. A percentage uptake difference less than or equal to 10 % between both mandibular condyles was considered acceptable.Result: The study cohort comprised 129 subjects (n=129), with 72(55.8%) males and 57(44.1%) females. Age ranged from 12 to 40 years (Mean±SD: 25.70±8.49). The mean mandibular condyle-to-clivus ratio on the right side was 0.97±0.12 and on the left was 0.98±0.13, which showed low variability (CV ~ 12 – 13%). However, the mean percentage difference in condylar uptake on both sides was 4.13±2.64 %, which showed very high variability (CV=63.92%). Gender-based comparison showed a significantly higher right condyle to clivus ratio in females (1.00±0.10) compared to males (0.94±0.12), with a p-value of 0.005 and a moderate effect size (Cohen’s d = -0.33).Conclusion: Determination of normal mandibular condylar uptake values in our population will contribute to enhanced diagnostic accuracy in maxillofacial applications of nuclear medicine, like condylar hyperplasia or Temporomandibular joint (TMJ) abnormalities.